Increased splenocyte proliferative response and cytokine production in β-endorphin-deficient mice - Refojo, Damian (2002)
We used β-endorphin-deficient mice as a novel approach to confirm the physiological role that opioid peptides play in the development or regulation of the immune system. We found that mice lacking β-endorphin possessed an enhanced immune response, measured in terms of splenocyte proliferation and interleukin (IL)-2 mRNA levels, in vitro production of the splenic macrophage inflammatory cytokines IL-6 and Tumor Necrosis Factor (TNF)-α and plasma IL-6 following lipopolysaccharide (LPS) administration. β-Endorphin-deficient mice had attenuated increases of plasma ACTH and corticosterone levels in response to LPS. These results are consistent with a postulated inhibitory role of endogenous β-endorphin on the immune system at multiple levels.